Sustainable Biodiesel Industry: A Techno-Economic Framework For Evaluating Biodiesel Production - Uhanto; Muhammad Syukri Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
This study evaluates the technical and economic aspects of the biodiesel industry, focusing on factors affecting production feasibility and industry sustainability. Secondary data for the analysis were sourced from published and Scopus-indexed research. The study identifies biodiesel characteristics, production processes, techno-economic aspects, and the biodiesel market. The analysis indicates that biodiesel has significant potential as an alternative to fossil fuels. It shares comparable energy density and cetane numbers with fossil diesel while providing superior lubrication properties and lower CO₂ emissions. Biodiesel transesterification achieves high efficiency with alkaline catalysts and feedstocks with low free fatty acid content, resulting in higher biodiesel yields. From an economic perspective, feedstock costs constitute 75–80% of the total biodiesel production cost, posing a major challenge due to the high price volatility of feedstocks in the market. Supportive policies for utilizing local and non-food feedstocks are necessary to reduce dependence on similar and relatively expensive raw materials. The financial sustainability of biodiesel production depends on production process efficiency and feedstock price stability. Economic feasibility is measured using indicators such as Net Present Value (NPV) and Internal Rate of Return (IRR). This knowledge provides valuable insights for developing more effective strategies in the biodiesel industry, supported by targeted policies that enhance both economic and environmental viability.